Anticipating independence, no premonition of partition. The lessons of bank branch expansion on the Indian subcontinent, 1939 to 1946. (17th March 2020) - Nguyen, Viet; Wolcott, Susan
Abstract: We examine investment in bank branches on the Indian subcontinent in 1939 and 1946. In 1947, the states of India and Pakistan were created from the erstwhile colony of British India. Partition was destabilizing to both economies. We use branch expansion as a proxy for entrepreneur's pre‐partition predictions of the future of these regions. Our results indicate there were no premonitions of economic dislocation. Banks tended to deepen their presence in regions which were already developed. But controlling for the level of 1931 development, branch placement was highest in exactly those regions, Bengal and the Punjab, which were to experience the greatest negative consequences from political division. After 1947, multiple banks failed; most failing banks were registered in the Punjab or Bengal region. In United India, businessmen saw as much promise in regions which were to become Pakistan as in regions which were to become India. After partition, the Pakistan regions were immediately more economically fragile. This event provides a general lesson. Economic integration had intensified over the years of British rule. The abrupt stop to integration harmed especially the smaller, less diversified region. Politicians should be wary of politically dividing regions which have evolved to function as integrated economic units.